Gender differences and relationships between upper extremity muscle strength, lower limb power and shuttle velocity in forehand smash and jump smash in badminton - Ferreira, A.; Górski, M.; Gajewski, J. (Acta of Bioengineering and Biomechanics, 2020)
Purpose: The aim of the study was to investigate the relationships between shuttlecock velocity during a badminton forehand smash with and without jump (VmaxWJ and VmaxNJ), strength of upper limb muscles, vertical jump height and to analyze differences in these parameters for each gender. Methods: The study examined members of the Polish National Badminton Team seven women and seven men.A special torque meter was used to assess the strength of the upper limb muscles. Vertical jumps were performed on an AMTI force plate.Shuttlecock velocity was measured using Vicon motion capture system. Results: Differences between the right and left limbs were observed in all muscle groups except shoulder flexion for both genders. The results of all measured parameters: torques, height of countermovement and spike jump (HACMJ, HCMJ, HSPJ), VmaxWJ and VmaxNJ, were greater for men than for women. No statistically significant differences were found between VmaxWJ (men: 83.27 ± 4.83 m/s; women: 67.57 ± 4.21 m/s) and VmaxNJ (men: 84.19 ± 6.05 m/s; women: 69.70 ± 6.53 m/s) withinthe same gender. Positive correlations were found between both HCMJ and HSPJ regarding VmaxWJ in men; the height of shuttlecock impact in jump smash (HWJ) and HSPJ in women; proving the importance of jumping ability in badminton. Negative correlations were found between HWJ and VmaxWJ for both genders. Conclusions: The jump before smash is not used in order to hit the shuttle from the highest point, but to gain time to correctly prepare the phase of stroke while being in the air.